Optimalisasi Proses Penerbitan Grosse Akta untuk Kapal Nelayan di Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas III Parepare - Ulia Fadhilah; Yustiani Frastika; Iksan Saifudin (Politeknik Pelayaran Sulawesi Utara, 2025)
The process of issuing a Grosse Akta (Grosse Deed) at the Parepare Class III Harbormaster and Port Authority Office is crucial for ensuring the legality of fishing vessels operating in the region. However, several obstacles often arise, slowing the process and increasing the administrative burden on fishermen. One major obstacle is incomplete documentation, which hinders the smooth running of the administrative process. Many fishermen do not fully understand the required documents and administrative procedures. This results in longer processing times for issuing a Grosse Akta. Technical issues also contribute to a hindering process, particularly those related to systems that are not yet well integrated. The continued use of manual recording in some parts of the process often leads to errors or inaccuracies in vessel data processing. Furthermore, a shortage of trained experts in handling administrative documents also contributes to the delay in completion times. To address these obstacles, this study suggests several strategic steps that can be taken to improve the efficiency of issuing a Grosse Akta. A comprehensive and easily understood guide for fishermen will assist them in properly preparing the required documentation. Simplifying the document format can also speed up the process, while improving consultation and help desk services will provide faster assistance to fishermen experiencing difficulties. Furthermore, digitizing the document management system will speed up workflows and reduce reliance on error-prone manual record-keeping. These steps are expected to improve the efficiency of the Grosse Akta publication process and provide better service to fishermen. By implementing these strategies, it is hoped that the Grosse Akta publication process will be more transparent and easily accessible to all fishermen.